Effects of cardiac rehabilitation on physical function and exercise capacity in elderly cardiovascular patients with frailty. Issue 4 (April 2021) - Ushijima, Akiko; Morita, Norishige; Hama, Tomoaki; Yamamoto, Asuka; Yoshimachi, Fuminobu; Ikari, Yuji; Kobayashi, Yoshinori
Highlights: Frailty is a major concern for mortality in elderly cardiovascular patients. Relieving frailty by cardiac rehabilitation leads to regain of physical function. Rehabilitation time for regain of exercise capacity is different from that for physical function. Optimal rehabilitation time for regain of exercise capacity needs future consideration. Abstract: Background: The effects of cardiac rehabilitation (CR) on long-term prognosis of cardiovascular disease (CVD) are well known. However, the effect of CR on frail CVD patients has not been fully addressed. Methods: This study consisted of 89 CVD patients with their age ≥65 years old (68 males, 75 ± 6 years), who participated in the outpatient CR program for 3 months. All the patients underwent cardiopulmonary exercise testing and the physical frailty was assessed using the Japanese Version of the Cardiovascular Health Study Standard before and after CR. Based on the assessment of frailty before CR, the patients were divided into the following two groups: frailty group (n = 23) and non-frailty group (n = 66: robust in 10 and pre-frail in 56 patients). Results: In the frailty group, 20 patients (87%) improved from frail status after CR, and usual walking speed, maximal grip strength, and lower extremity strength were significantly improved (1.06±0.20 vs. 1.20±0.18 m/sec, p <0.001; 21.7 ± 5.5 vs. 23.6 ± 6.3 kg, p <0.01; 0.37±0.09 vs. 0.43±0.11 kgf/kg, p = 0.001, respectively), but peak VO2 did not change after CR (15.9 ± 3.1 vs. 16.2 ± 3.8 ml/min/kg, NS). In the non-frailty group, all these parameters were significantly improved after CR (1.24±0.19 vs. 1.29±0.23 m/sec, p <0.05, 28.7 ± 7.0 vs. 30.2 ± 7.3 kg, p <0.001, 0.50±0.18 vs. 0.54±0.13 kgf/kg, p <0.05, 17.7 ± 4.7 vs 18.5 ± 4.2 ml/min/kg, p <0.01, respectively). Conclusion: Short-term CR could obtain the improvement of the physical function, providing the prerequisite step for possibly following improvement of exercise capacity in elderly CVD patients with frailty. It may be inferred that longer duration of CR would be needed to obtain the improvement of exercise capacity in these patients, being the future consideration to be determined.